Efficiency of Remaxol Use in Supporting Treatment of Advanced Tuberculosis - V. M. Kolomiets; A. L. Kovalenko; E. V. Talikova (Антибиотики и Химиотерапия)
The aim of this study was to evaluate effectiveness of remaxol inclusion in the supporting therapy regimen in patients with the fibrous-cavernous form of drug-resistant tuberculosis. Treatment of 173 patients with fibrous-cavernous pulmonary tuberculosis was analyzed. Standard clinical laboratory methods and x-ray diagnostic were conducted in all patients as well as the spectrum of pathogen sensitivity to anti-tuberculosis drugs was defined. Changes in immune status and state of liver detoxification function were evaluated in dynamics (before and after hepatoprotective therapy course) taking in consideration level of cytokines (interleukins 1,4,6 and 10, tumor necrosis factor, interferon-gamma) and liver enzymes (AST, ALT). Two groups of patients were formed using randomization: group 1 (main) with 111 patients who received etiotropic therapy and complex of treatment and rehabilitation activities, and group 2 (comparisons) with 62 patients who, in addition to the main complex of therapy, received remaxol: intravenously, 400 ml once a day, a course of 12 droppers. In this research it was revealed that remaxol inclusion in the supporting treatment regimen showed hepatoprotective (improved transaminase) and minor immunoprotective (positive cytokine profile) effects. The obtained laboratory results correlate with clinical data: prevalence of high (53.8%) and absence of low treatment efficacy cases and a higher degree of patients adherence to treatment.